The history of the development of kinesiology - Klochko, O. (ХДАК, 2023)
The abstract considers the issue of the history of the development of the science of kinesiology, which at the present stage is an alternative to traditional medicine. Methods of detecting disorders in the body using applied kinesiology are described. A conclusion is made about the relevance and effectiveness of this method in modern practice.
Keywords: kinesiology